Lecturer and student satisfaction with learning support at the College of Law and Government, Sisaket Rajabhat University, for the Academic Year 2021: Lecturer and student satisfaction with learning support at the College of Law and Government, Sisaket Rajabhat University, for the Academic Year 2021 - saweangmee, luesak (RATANABUTH JOURNAL, 2024)
Higher education institutions have four primary missions: producing graduates, conducting research, providing academic services to society, and preserving arts and culture. The successful execution of these missions is crucial for both short-term and long-term national development. To maintain high standards, these institutions must demonstrate their ability to develop knowledge and produce graduates who align with the country's strategic development goals. The learning environment plays a significant role in this process, as a positive atmosphere enhances students' mental health, motivation, and attitudes, leading to more effective learning. This study involved a sample of 291 individuals, including 22 lecturers and 269 students from the College of Law and Administration at Sisaket Rajabhat University during the 2021 academic year. Data were collected using interviews, teacher satisfaction questionnaires, and student learning support questionnaires. Quantitative data were analyzed using descriptive statistics, and qualitative data were analyzed using content analysis methods. Results indicated that among the lecturers, 63.6% were male, and 36.4% were associated with the field of Political Science. Among the students, 62.1% were female, with 40.5% studying Political Science. The majority of student respondents were in their second year. Instructor satisfaction with service provision was high ( =3.68, S.D =0.73). Student satisfaction with learning support was also high ( =3.87, S.D =0.79). Obstacles: Audiovisual equipment in the classroom is not complete and ready for use. The environment around the building when it rains heavily often has problems with the stairs in front of the building being flooded, making the stairs slippery and risking danger to students and staff. There are few drinking water service points in each classroom. Maintaining the water supply system in the faculty building to meet standards and the faucets are often broken. Supporting items in the classroom, such as computers, microphones, and equipment, should be ready for use. A projection screen should be added in every room where teaching is being taught. Safety equipment, such as fire extinguishers, should be added. There should be a specific room for students to work and consult with teachers outside of class time. I would like the university to prepare teaching documents when the semester starts.